Therapeutic Uses of Euphorbia thymifolia: A Review - Gupta, Bhavna; Srivastava, Rashmi S.; Goyal, Radha (Pharmacognosy Reviews)
The extracts of many plants used in traditional medicine contain curative agents That is used in many modern medicines. As part of the quest for potentially valuable Plants of medicinal value. In Sanskrit Euphorbia thymifolia means “Laghu dudhika or Raktavindachada”. The Euphorbia thymifolia widely used in the Ayurveda to cure many remedies. The leaves and seeds are given in worm case and in certain bowel affection of children. In India they are considered as stimulant and laxative also use in many disease due to presence of different constituents.
Keywords: Euphorbia thymifolia; Hydrolysable Tannins; Antioxidant; Antiviral